Corporate Real Estate Alignment - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
This dissertation aims to enhance CRE alignment by approaching alignment as a design and decision process as is explained in chapter 1. The current state of the art in CRE alignment modeling is summarized in paragraph 2.1. This sets the context of this research and will show that CRE alignment is complex and multidimensional. Thereafter, an assessment of CRE alignment models from a design and decision perspective is made in paragraph 2.2. Based on this perspective I identified the scientific gap of this PhD research. Most of the work in this chapter has been published before in the last 10 years. Figure 2.1 shows the timeline of the important publications related to the two topics that this chapter addresses: 1 State of the art of modelling CRE alignment processes; 2 Assessment of structure models of CRE alignment from a design and decision perspective. As can be seen in the figure below, the different topics have evolved at the same time. I have chosen to structure the chapter around the two topics and not follow the order of publication. Because the topics have evolved over time this causes some redundancy in and between paragraph 2.1 and 2.2. In the last paragraph 2.3 conclusions, they are brought together. But before showing the state of the art, CRE and CREM are defined. Corporate real estate is a specific type of real estate. CoreNet Global (2015) describes it as the real estate necessary to conduct business—the bricks and mortar of office buildings, manufacturing plants and distribution centres, retail stores, and similar facilities. It can include owned or leased space, buildings, and infrastructure, such as power plants or even airport runways. Corporate real estate is closely related to commercial real estate, however, there is a distinct difference in business objectives. In the commercial real estate world, the business is the real estate. The goal for commercial real estate is to provide a risk adjusted return to the investor; whereas, in corporate real estate real estate supports the business function. In other words, corporate real estate represents the demand side or user side of real estate, while commercial real estate focuses on the supply side to meet that need. Corporate real estate is seen since 30 years by (Joroff, 1993) as the fifth resource of the business that needs to be managed besides capital, human resources, IT and communication. One of the big challenges in corporate real estate management is reducing the gap between the high speed of business and the slow speed of real estate, i.e. between the so-called dynamic real estate demand and the relatively static real estate supply. A decade later (Krumm et al., 2000, p. 32) described CREM as “The management of a corporation’s real estate portfolio by aligning the portfolio and services to the needs of the core business (processes), in order to obtain maximum added value for the business and to contribute optimally to the overall performance of the corporation”. One could say that the authors position CRE alignment in this definition as the raison d’être of CREM. Other authors (Heywood & Arkesteijn, 2017) position CRE alignment as one of the activities that CREM needs to perform. In this research, CREM will be seen as a wide range of activities that must be performed by the corporate real estate manager, while the alignment of CRE with the business will be seen as one of CREM’s activities and is referred to as CRE alignment.